KONSTRUKSI MAKNA IKLAN AQUA EDISI ‘’AQUA LIFE’’ #BijakBerplastik, Inovasi pertama di Indonesia - ASIMA OKTAVIA SITANGGANG (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Advertising is one form of mass communication that seeks to construct events in society and the cultural value in them into a form based on certain themes, images and symbolic meanings. AQUA LIFE #BijakBerplastik, trying to move consumers to participate in the campaign that they launched since June 5, 2018 in connection with the reduction of plastic waste by using recycled plastic on Aqua packaging 100% recycled. By using Roland Barthes's semiotic analysis method, the writer found several meaning constructions of AQUA LIFE #BijakBerplastik with 60 seconds duration. This ad not only invites consumers to contribute to continuing the good for the earth by reducing plastic waste but also reinforces the construction of its branding strategy which is reflected in two main myths: (1) Aqua's consistency in providing services and building customer loyalty; (2) Aqua's brand personality that is pure, committed and cares for the environment.